복강경 충수 절제술과 개복 충수 절제술의 임상적 비교 - 이시연(See Youn Lee); 박용검(Yong Gum Park); 장인택(In Taik Chang) (Annals of surgical treatment and research, 2004)
Purpose: Nowadays laparoscopic appendectomy is widely practiced in developed countries. The purpose of this study was to evaluate laparoscopic appendectomy in comparison with open appendectomy. Methods: On hundred cases each of laparoscopic appendectomy and open appendectomy, performed between February 2001 and June 2002, were reviewed for age, sex, operative time, hospital days, time for first meal, number of used parenteral analgesia, number of OPD visits, etc. Results: Operative time was longer in the laparoscopic appendectomy group (P＞0.05) and the number of used parenteral analgesia was slightly higher in the laparoscopic group (P＞0.05). However, recovery time for diet was slightly shorter in the laparoscopic group (P＞0.05). None of these trends were statistically significant. The times of OPD visit after discharge was less in the laparoscopic group (P＜0.05). The hospital days of pathological simple appendicitis were shorter in the laparoscopic appendectomy group (P＜0.05). In the laparoscopic group, intraabdominal abscess was developed in 2 cases, wound infection in 4, and intestinal obstruction in 2. The conversion rate to open appendectomy was 7% (7/100) in the laparoscopic group. Conclusion: Laparoscopic appendectomy can shorten overall OPD follow up days and in case of simple appendicitis, laparoscopic appendectomy can also shorten hospital days. KCI Citation Count: 4